UREA MOLASES BLOK SEBAGAI PAKAN SUPLEMEN UNTUK TERNAK KAMBING LOKAL PADA BERKAH MANDIRI FARM DESA PEJAMBON KECAMATAN NEGERI KATON - Andre Meiditama Kasenta; Agung Adi Candra; Riko Noviadi; Nani Irwani; Nurul Azizah Usman; Lisa Aprilia (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
Feed availability and quality are critical factors affecting the productivity of small ruminant livestock. In smallholder farming systems, feed management remains a major constraint due to limited availability of quality forage, seasonal fluctuations in feed supply, and low adoption of feed processing technologies. Similar challenges were identified in the Berkah Mandiri Farm farmer group in Pejambon Village, Negeri Katon District, Pesawaran Regency, where traditional goat husbandry and simple feed management practices are still commonly applied. This community service program aimed to enhance farmers’ knowledge and skills through the introduction and application of Urea Molasses Block (UMB) as a feed supplement for local goats. The activities were conducted through extension sessions, hands-on training on UMB production, and evaluation using questionnaires. The results showed that farmers were able to independently produce UMB and understand its benefits as a supplementary source of nutrients. Overall, participants’ level of understanding regarding feed technology and UMB reached 75%, categorized as “good understanding”. The application of UMB technology is expected to improve feed management, enhance the productivity of local goats, and support the sustainable development of smallholder goat farming.